Betrayal of the spirit : my life behind the headlines of the Hare Krishna movement - Muster, Nori J. (Nori Jean), 1956- (Urbana : University of Illinois Press, 1997)
Combining behind-the-scenes views of an often besieged religious group with a personal account of the author's struggle to find meaning in it, Betrayal of the Spirit takes the reader closer than any other source so far to the reality of life in the Hare Krishna movement. Nori J. Muster, a California native, joined the International Society of Krishna Consciousness (ISKON) - the Hare Krishnas - in 1977, shortly after the death of the movement's spiritual master, Srila A. C. Bhaktivedanta Swami Prabhupada. She lived in the Krishnas' western world headquarters in Los Angeles and worked for ten years as a public relations secretary and editor of the organization's newspaper, the ISKON World Review.
Her story of the Hare Krishnas' decline is a gripping presentation of facts gleaned from personal reminiscences, published articles, and internal documents. Betrayal of the Spirit details drug dealing, weapons stockpiling, deceptive fund-raising, child abuse, and murder within ISKON, as well as the dynamics of schisms that forced some 95 percent of the group's original members to leave. Although the movement fell into disarray after the death of its founder, the author's story is one of a continual search for truth and religious meaning as an ISKON member. Muster's account of the scandal-plagued decade following Swami Prabhupada's death ends in 1988 when, disillusioned over the continuing internal strife and scandals, she left her job and the movement.
Includes bibliographical references (pages [197]-206) and index.
Description based on print version record.
Keywords: International Society for Krishna Consciousness; Muster, Nori J. -- 1956-; Hare Krishnas -- United States -- Biography; Erlebnisbericht; RELIGION / Comparative Religion; Electronic books